Two new species of Hygrocybe subgenus Pseudohygrocybe (Hygrocybaceae, Agaricales) from southwestern China - Li, Dong-Mei; Yang, Zhu L. (Phytotaxa, 2026)
Species diversity of Hygrocybe in China has frequently been documented in the last decades, but many species remain unknown. During a fungal diversity survey, we collected some specimens of Hygrocybe subgen. Pseudohygrocybe in southwestern China. Based on integrated morphological data, ecological features, and phylogenetic analyses using the nuclear ribosomal internal transcribed spacer region ITS1-5.8S-ITS2 (ITS) and the nuclear ribosomal RNA large subunit (LSU) sequences, we describe two new species here. Hygrocybe sinorubra is characterized by small to medium-sized, China-red basidiomata covered with minute squamules and ovoid basidiospores. Hygrocybe cortinarioides is distinguished by its coral-red, squamulose pileus, occasional arachnoid veil, pruinose stipe apex, and small ellipsoid to elongate basidiospores. This study not only expands the known species number of subgen. Pseudohygrocybe to 58 but also highlights the need for further research to clarify the full diversity of this group in southwestern China.